Genetics and bioethics in Latin America - Vergès, Claude (Acta Bioethica, 2004)
The relations between genetics and bioethics in Latin America are analyzed through the relations between scientific power and human rights in the particular conditions of this continent. Particularly, the myth of genetics'power to reach perfect health is allowing abuses of human rights in poor democratic societies. The analysis of the recommendations of the World Health Organization for genetic counseling and genetic probes shows that bioethics must be vigilant in its applications.